Public policies to promote sustainable development in tradicional communities in amazon (Desenvolvimento em Questão, 2025)
With the emergence of the concept of sustainable development, public policies aimed to promote this development model proliferated from the 1990s onwards. From the beginning of the 2000s, policies that, in addition to seeking the sustainable development also had as focus on traditional communities, gained special attention, giving rise to new concepts as like sociobiodiversity and, most recently, bioeconomy. In that regard, study aims to present the process of project construction implemented through public policies geared towards promoting sustainable development in traditional communities in Amazon, based on a case study conducted in the Ererê Community, located within an Environmental Protection Area in the state of Pará, Brazil. Furthermore, the paper intends to identify the predominant categories within each public policy implemented in the studied community, as well as the public policy approach utilized. Methodologically the study had a qualitative approach with the use of various participatory instruments for collecting data and information. The results showed that the discontinuation of projects was a fundamental factor hindering the full effectiveness of the public policies. Even projects with a multicentric approach didn’t guarantee the full participation of all actors, a phenomenon that warrants further investigation in future studies, given the probable unequal power relations involved.
Keywords: Ererê Community; Case study; Environmental preservation area; Sociobiodiversity; Bioeconomy